Keefektifan Konseling Realita untuk Mengatasi Kecemasan Mengemukakan Pendapat pada Siswa SMP - Dwi Istiqomah; Bakhrudin All Habsy (Indonesian Journal of Educational Counseling, 2019)
THE EFFECTIVENESS OF REALITY COUNSELING TO OVERCOME ANXIETY EXPRESSING OPINIONS FOR JUNIOR HIGH SCHOOL STUDENTS. This study aims to test the effectiveness of reality counseling to overcome the level of anxiety express opinions of students in junior high. This research uses pre experimental pre-test type post test one group design. The data analysis used is paired test of T-test, to see the change of anxiety level in experimental group between pretest and post test by looking at t table price at degrees of freedom (dk), that is the magnitude is N-1, and at a significant level α = 0,05 (95%) then we get t-table = 1,833, assuming if t count> t-table then Ha “received”. From the test results using T-Test proves that effective reality counseling in overcoming anxiety expressed the opinion of junior high school students. Because t arithmetic 16,628> t table 1,833 on the significant level α = 0,05, then Ha “accepted”. Based on the findings of the research, for the next researcher, with the findings of reality counseling implementation to overcome the level of anxiety to express the opinion of the students, should be an inspiration in doing further research by applying counseling with other therapies, especially in an effort to overcome the anxiety level express opinion to the students.